Comprehensive Evaluation and Dynamic Evolution Characteristics of Tourism Ecological Security Using the DPSIR-DS Model in the Yangtze River Economic Belt, China - Yue Pan; Jia Wang; Zhaolong An; Jianpu Li; Gangmin Weng (SAGE Open)
The Yangtze River Economic Belt (YREB) is positioned as the main battlefield of ecological priority and green development in China. It is of great significance to dynamically grasp the situation of tourism ecological security in YREB for promoting the green and high-quality development of regional tourism. Aiming at the disadvantage of either-or in evaluation research, this study established the index system based on the inter-period DPSIR framework, designed an integrated assessment model combining the entropy method, the membership function, and the D-S evidence theory model to assess the tourism ecological security level from the perspective of probability value, then revealed its spatiotemporal dynamics characteristics. Results showed that: (1) the regional security level is in a good trend of weakening fluctuations and stable improvement, in which the upstream and downstream improvement is more significant, but still at a lower level in general. (2) The security levels of the 11 areas included were all located at Risk level to Relative Security level with significant differences, including Zhejiang, Anhui, Hubei, and Chongqing were the key ecological nodes for tourism ecological security improvement. (3) The transitions among security levels were frequent, while the higher levels were relatively unstable, implying that the tourism ecology has not improved in essence. Finally, strategic suggestions for improving tourism ecological security are proposed in terms of building joint prevention and control mechanisms, clarifying risk factors, and innovating protection paths.